2015
DOI: 10.1177/2048872615570770
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and ischemia-reperfusion injury in ST segment elevation myocardial infarction

Abstract: Background: Models of experimental ischemia-reperfusion (IR) in adiponectin knockout animals have shown that adiponectin mediates protection against the development of IR injury. However, the role of adiponectin in IR injury in humans is largely unknown. Methods: In a total of 234 ST segment elevation myocardial infarction (STEMI) patients, baseline circulating total adiponectin concentration was correlated with IR injury after primary percutaneous coronary intervention (pPCI) and with major adverse cardiac ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Myocardial I/R injury could result in heart dysfunction. [22] In the present study, monitoring hemodynamic parameters showed that a reduction in cardiac systolic function was indicated by the I/R-induced decreases of LVSP and +dp/dtmax in the isolated hearts. And the decreased Àdp/dtmax and the increased LVEDP suggested the I/Rproduced a decrease in cardiac diastolic function.…”
Section: Discussionsupporting
confidence: 53%
“…Myocardial I/R injury could result in heart dysfunction. [22] In the present study, monitoring hemodynamic parameters showed that a reduction in cardiac systolic function was indicated by the I/R-induced decreases of LVSP and +dp/dtmax in the isolated hearts. And the decreased Àdp/dtmax and the increased LVEDP suggested the I/Rproduced a decrease in cardiac diastolic function.…”
Section: Discussionsupporting
confidence: 53%
“…Relevant literature reports that nearly 60% of patients after PCI are severely deficient in exercise, and about 84% of patients after PCI have associated anxiety symptoms, while 67% have associated depressive symptoms [26,28]. Previous studies have shown that myocardial ischemia-reperfusion (IR) injury can cause ventricular cell death and is a major pathological event leading to morbidity and mortality in those with acute myocardial infarction [11,12]. Interestingly, appropriate exercise can rapidly produce a cardiac phenotype that resists IR-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that myocardial ischemiareperfusion (IR) injury can cause ventricular cell death and is a major pathological event leading to morbidity and mortality in those with acute myocardial infarction [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…PARP inhibitors were demonstrated to ameliorate all these effects in various experimental systems [172][173][174]. Acute myocardial infarction is followed by reperfusion, due to either coronary thrombolytic therapy or surgical intervention [175]. However, the return of oxygen to a respiratory chain that has suffered hypoxic damages during the preceding ischemia results in a substantial perfusion injury characterised by massive ROS and RNS production, upregulated expression of inflammatory cytokines, and PARP activation [176].…”
Section: Atherosclerosis and Myocardial Infarctionmentioning
confidence: 99%